Environment and Citizenship in Latin America: A New Paradigm for Theory and Practice - Latta, Alex; Wittman, Hannah (European Review of Latin American and Caribbean Studies, 2010)
As a reflection of the ecological pressures associated with rapid modernization and globalization, the environment has become an enduring theme of public debate and protest in Latin America. Over the past decade, scholars have made increasing connections between such debate and a range of questions related to citizenship. Meanwhile, a discourse of ‘environmental citizenship’ has a growing prevalence in policy across the region. While these developments echo similar political and academic trends in the Global North, the Latin American context demands a unique set of theoretical and methodological approaches to studying the intersection of ecology and citizenship, sensitive to the specific historical, cultural, and ecological character of the region. We outline a research agenda spanning questions of land, identity and citizenship; environmental justice and de-colonization; social subjectivity and the state; urban natures and citizens; and the materiality/subjectivity of nature. This array of approaches points to a more acute conceptualization of citizenship, both in terms of its understanding of politics and its treatment of ecology; it also offers a point of view that recognizes citizens and natures as dynamic realities, which mutually condition each other in a sphere of ongoing contest. Resumen: Medio ambiente y ciudadanía en América Latina: un nuevo paradigma para la teoría y prácticaComo reflexión de los impactos ecológicos asociados con la modernización rápida y la globalización, el medio ambiente se ha transformado en un tema de debate y protesta constante en Latinoamérica. Durante la última década, un número creciente de académicos ha observado conexiones entre tal debate y una gama de asuntos relacionados con la ciudadanía. Al mismo tiempo, un discurso de ‘ciudadanía ambiental’ ha alcanzado una prevalencia notable en las políticas públicas de la región. Aunque estos acontecimientos reflejan de una tendencia política e intelectual similar ocurrente en el norte global, el contexto latinoamericano nos exige un conjunto especial de enfoques teóricos y metodológicos para examinar la intersección de ecología y ciudadanía, con una sensibilidad hacia el carácter histórico, cultural y ecológico de la región. Proponemos una agenda de investigación que abarque los temas de tierra, identidad y ciudadanía; justicia ambiental y de-colonización; subjetividad social y el estado; naturaleza y ciudadanía en las urbes; y la materialidad/ subjetividad de la naturaleza. Esta serie de planteamientos nos lleva hacia una conceptualización más nítida de la ciudadanía, tanto en su compresión de la política como en su consideración de la ecología; nos ofrece además una mirada que registra al ciudadano y a la naturaleza como realidades dinámicas, que se condicionan mutuamente en un ámbito de contienda perpetua.